Penerapan Pembelajaran Inovatif Untuk Meningkatkan Motivasi Dan Hasil Belajar Bola Voli Kelas VIII D Pada SMP Negeri 12 Surakarta - Wibisono, Kurniawan Ari; Guntur, Guntur (Jayapangus Press, 2025)
Based on student observations in learning volleyball in class VIII D SMP Negeri 12 Surakarta, there are problems with student motivation and less innovative learning methods. On the other hand, the heavy ball causes students' hands to feel pain when performing technical movements or strokes, so it is necessary to innovate methods and media. The purpose of this study was to determine whether sponge plastic ball aids can increase volleyball learning activities, whether sponge plastic ball aids can improve volleyball learning outcomes. The research method is Classroom Action Research (PTK) which is carried out in two cycles. The research population was class 8D students of SMP Negeri 12 Surakarta, totaling 32 students. The research instruments were interview guidelines, questionnaires, and observation sheets. The data analysis technique used was quantitative descriptive analysis. The results showed that sponge plastic ball aids can improve volleyball learning activities, sponge plastic ball aids can improve volleyball learning outcomes. This is evidenced in the results of cycle I which showed an increase in the assessment of the knowledge aspect, there were 23 students (71.87%) who were complete and those who did not meet the criteria were 9 students (28.13%), the skill aspect showed an increase, namely 23 students (71.87%) in the complete category and 9 students or (28.13%) were not complete. In cycle II there was an increase in each aspect of better student learning, this was evidenced by the knowledge aspect showing an increase, namely 30 students (93.75%) in the complete category and 2 students (6.25%) in the incomplete category.